نموذج مقترح لمستودع رقمي تعليمي لتطوير المنتج النهائي لمقرر التربية الميدانية وفق احتياجات أعضاء هيئة التدريس في ضوء استراتيجية تقويم الأقران - مجاهد، سهام عبدالحافظ (رابطة التربويين العرب, 2015)
يهدف البحث إلى وضع نموذج مقترح لمستودع رقمي تعليمي لمنتجات طلاب تكنولوجيا التعليم المقرر التربية الميدانية في ضوء إستراتيجية تقويم الأقران ووفقا لاحتياجات أعضاء هيئة التدريس. ولقد تم إتباع المنهج الوصفي لتحديد احتياجات أعضاء هيئة التدريس حيث تم تصميم إستبيانة وتطبيقها على عينة عشوائية من أعضاء هيئة التدريس عددها (30) عضو كما تم تصميم إستمارة لتحديد معايير فحص المنتج النهائي (كائنات التعلم)، وأخرى لتحديد مؤشرات نجاح أداء المستودع الرقمي المقترح وتم تطبيقهما على نفس العينة السابقة. وفي ضوء ما تم التوصل إليه من نتائج تم تحليل الإستمارات السابقة ووفقاً للبنود التي حصلت على تقدي عال أو فوق المتوسط تم وضع التصور المقترح ليلبي احتياجات أعضاء هيئة التدريس مشتملا على المحاور الرئيسية لمؤشرات نجاح أداء المستودع الرقمي لمنتجات الطلاب من التربية العملية ووفقاً لإستراتيجية تقييم الأقران.
The research aims to develop a proposal for repository model digital educational products for technology education student’s decision education field according to the peers’ assessment , according to the needs of faculty member’s strategy. We have been following the descriptive approach to determine the needs of the faculty members by designing questionnaire and applying to a random sample of faculty members of (30) member. In addition, a form is designed to determine the final product examination standards (learning objects), and another one to determine the success of the performance of the repository digital proposed indicators. Both of them were applied to the same previous sample .In light of what has been reached by the results of the previous forms analysis and in accordance with the terms of which got high esteem or above average was proposed visualization mode to meet the needs of faculty having the main axes of the indicators of success is the performance of the repository of digital products students from practical education according to the strategy peer assessment.
Keywords: تكنولوجيا التعليم -- التربية العملية -- هيئة التدريس -- التعليم الإلكتروني